GE_GERICHTE P/18865/2009 vom 26. März 2015 - GE Cour de justice (2015)
ESCROQUERIE; ABUS DE CARTES-CHÈQUES; CARTE DE CRÉDIT; PEINE PRIVATIVE DE LIBERTÉ; RESPONSABILITÉ RESTREINTE(DROIT PÉNAL) | CP.146.1; CP.146.2; CP.148; CP.251; CP.110.4; CP.219; CP.47; CP.42.1; CP.49; CP.19.2; CPP.126.1; CO.41; CP.69